Pengaruh Audit Komunikasi Terhadap Efektivitas Krasida (Kredit Angsuran Sistem gadai) Pada PT. Pegadaian Kanwil VI Makassar - Fikri Afifah , Adzra; Zeflia, Zelfia (RESPON JURNAL ILMIAH MAHASISWA ILMU KOMUNIKASI, 2022)
This study aims to determine the ongoing communication audit process and the influence of the communication audit on the effectiveness of the Krasida Program (Installment Credit System Pawn) at PT. Pawnshop Regional Office VI Makassar. This research uses quantitative method. The results showed that the Communication Audit Process Communication Audit Process that took place at PT. Pegadaian Kanwil VI Makassar is going well, because employees can provide accurate and clear information to customers using the media and customers receive and understand the information conveyed well. Delivery of messages from PT. Pegadaian Kanwil VI Makassar to customers has a significant influence and communication between employees and customers runs effectively. Communication audits can make communication between people i an organization effective so that goals will be achieved and get maximum results an organization effective so that goals will be achieved and get maximum results.